1990
DOI: 10.3146/i0095-3679-17-1-7
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Fatty Acid Content in Peanut Oil1

Abstract: The stability or shelf-life of peanut (Armhis hypogaea L.) oil is related to the fatty acid content of the oil, with the major factor being the ratio of oleic (C18:l) to linoleic (C18:2) acid (OK ratio).To obtain information needed for development of cultivars with improved oil quality, eight parents representing a range in oleic and linoleic content were crossed in diallel. Individual F, seeds (F, embryos) from the greenhouse and F, bulk seed from the 56 crosses grown in the field were analyzed to determine l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 16 publications
1
32
1
1
Order By: Relevance
“…Similar correlations have been reported in previous studies (Dwivedi et al, 1993;Hammond et al, 1997;Anderson et al, 1998). Mercel et al (1990) has also suggested that fatty acid composition should not affect the oil content of seed.…”
Section: Correlations Among Oil Fatty Acidssupporting
confidence: 90%
“…Similar correlations have been reported in previous studies (Dwivedi et al, 1993;Hammond et al, 1997;Anderson et al, 1998). Mercel et al (1990) has also suggested that fatty acid composition should not affect the oil content of seed.…”
Section: Correlations Among Oil Fatty Acidssupporting
confidence: 90%
“…In the US, Runner, Virginia, Spanish, and Valencia markettype peanuts are commercially grown. The peanuts kernel contains ∼52% oil by weight [1], which is rich in monounsaturated (MUFA) and polyunsaturated fatty acids (PUFA) [2]. The high-oleic peanut genotype, whose acreage in the US has been increasing consistently over the past five years, contains upwards of 80% oleic and 5% linoleic acids [3].…”
Section: Aaphmentioning
confidence: 99%
“…Therefore, the additive-dominance genetic model was adequate for all the traits [22] and it was concluded that both kinds of gene effects were important for controlling the inheritance of all the traits studied [12]. Significant effects of GCA and SCA have also been reported for the inheritance of different fatty acids in oil castor [14], peanut [13], sunflower [23] and Brassica juncea L. [24]. The greater importance of SCA compared to GCA has been reported in peanut oil for oil quantity and quality [13].…”
Section: Resultsmentioning
confidence: 99%
“…Improving oil yield requires adequate information regarding the nature of general combining ability (GCA) and specific combining ability (SCA) of the parents available in a wide array of genetic material to be used in the hybridization programs. Information is also required about the nature of gene actions involved in the expression of quantitative and qualitative traits [13,14]. Diallel analysis provides a unique opportunity to test a number of lines in all possible combinations [12].…”
Section: Introductionmentioning
confidence: 99%